2022
DOI: 10.3390/buildings12091436
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Fibres on the Mechanical and Durable Behaviour of Fibre-Reinforced Concrete

Abstract: Numerous studies have been conducted recently on fibre reinforced concrete (FRC), a material that is frequently utilized in the building sector. The utilization of FRC has grown in relevance recently due to its enhanced mechanical qualities over normal concrete. Due to increased environmental degradation in recent years, natural fibres were developed and research is underway with the goal of implementing them in the construction industry. In this work, several natural and artificial fibres, including glass, ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 63 publications
0
16
0
Order By: Relevance
“…Different types of PFs absorb water differently. More et al [ 40 ] found that the water absorption of coir, jute, and sisal fibers was 130–180%, 20–40%, and 75–80%, respectively. Wei et al [ 57 ] found that sisal fiber water absorption in Ca(OH) 2 solution increased by 5% compared to ordinary water.…”
Section: Pf-reinforced Geopolymer Compositesmentioning
confidence: 99%
See 2 more Smart Citations
“…Different types of PFs absorb water differently. More et al [ 40 ] found that the water absorption of coir, jute, and sisal fibers was 130–180%, 20–40%, and 75–80%, respectively. Wei et al [ 57 ] found that sisal fiber water absorption in Ca(OH) 2 solution increased by 5% compared to ordinary water.…”
Section: Pf-reinforced Geopolymer Compositesmentioning
confidence: 99%
“…Due to repeated expansion and contraction of PFs under the action of water, stress is generated inside the fibers, and microcracks are formed [ 40 ]. When free water enters PF cells, hydrogen bonds are formed between water and PF, so as to compound the fiber and matrix interface under the action of water [ 58 , 59 ].…”
Section: Pf-reinforced Geopolymer Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…Tiberti et al [ 26 ] explored the ability of fibers in controlling cracks by discussing more than ninety tension tests on reinforced concrete prisms. More et al [ 27 ] investigated the mechanical and durability qualities of fiber-reinforced concrete (FRC) experimentally with the optimum fraction, and a constitutive model for the analysis of reinforced concrete structures was modified to improve its computational efficiency [ 28 ]. Tamrazyan et al [ 29 ] studied the solution of the analysis of the stress–strain state of FRC structures under emergency dynamic effects.…”
Section: Introductionmentioning
confidence: 99%
“…Aziz et al [11] offered the current past and present studies and improvements for the effective usage of natural fibers from wood, jute, bamboo, sugarcane bagasse, sisal, plantain, muamba, and coconut husk for making concrete. More and Subramanian [12] studied the influence of fibers on the durability and mechanical characteristics of fiber-reinforced concrete. Machaka et al [13] examined the influence of employing fan palm natural fibers on the durability and mechanical properties of concrete.…”
mentioning
confidence: 99%